Key Components of Different Plant Defense Pathways Are Dispensable for Powdery Mildew Resistance of the Arabidopsis mlo2 mlo6 mlo12 Triple Mutant - Kuhn, Hannah; Lorek, Justine; Kwaaitaal, Mark; Consonni, Chiara; Becker, Katia; Micali, Cristina; Ver Loren van Themaat, Emiel; Bednarek, Paweł; Raaymakers, Tom M.; Appiano, Michela; Bai, Yuling; Meldau, Dorothea; et al. (Frontiers in Plant Science, 2017)
Loss of function mutations of particular plant MILDEW RESISTANCE LOCUS O (MLO) genes confer durable and broad-spectrum penetration resistance against powdery mildew fungi. Here, we combined genetic, transcriptomic and metabolomic analyses to explore the defense mechanisms in the fully resistant Arabidopsis thaliana mlo2 mlo6 mlo12 triple mutant. We found that this genotype unexpectedly overcomes the requirement for indolic antimicrobials and defense-related secretion, which are critical for incomplete resistance of mlo2 single mutants. Comparative microarray-based transcriptome analysis of mlo2 mlo6 mlo12 mutants and wild type plants upon Golovinomyces orontii inoculation revealed an increased and accelerated accumulation of many defense-related transcripts. Despite the biotrophic nature of the interaction, this included the non-canonical activation of a jasmonic acid/ethylene-dependent transcriptional program. In contrast to a non-adapted powdery mildew pathogen, the adapted powdery mildew fungus is able to defeat the accumulation of defense-relevant indolic metabolites in a MLO protein-dependent manner. We suggest that a broad and fast activation of immune responses in mlo2 mlo6 mlo12 plants can compensate for the lack of single or few defense pathways. In addition, our results point to a role of Arabidopsis MLO2, MLO6, and MLO12 in enabling defense suppression during invasion by adapted powdery mildew fungi.